Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Olshop Pakaian - Feronika Dalla; Usman Usman (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to determine the analysis of marketing strategies in increasing clothing online shop sales that utilize social media such as Facebook, Instagram and Whatsapp which can increase clothing online shop sales. This research was conducted in Bengkayang, Bengkayang Regency, West Kalimantan, using qualitative research with a descriptive approach. Data collection techniques are carried out using direct interviews, observation and documentation. The results of this research show that analysis of marketing strategies in the use of social media is considered to be a form of marketing strategy chosen by Clothes Shop to increase the achievement of marketing goals, one of which is increasing sales of Clothes Shop quite effectively, because most consumers more often use the Whatsapp media application. , Instagram and Facebook to place online clothing orders. The marketing strategy that most influences consumers is promotion through social media and this influences consumers to buy clothing online shop products, for this reason clothing online shops need to develop further marketing strategies in improving clothing online shops so that they can influence consumers' buying interest more optimally.